2020
DOI: 10.3390/app10041281
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a Coupled Hydrologic and Hydraulic Model to Simulate Surface Water and Groundwater Hydrology in a Typical North-Eastern Germany Lowland Catchment

Abstract: Lowland river basins are characterised by complex hydrologic and hydraulic interactions between the different subsystems (aerated zone, groundwater, surface water), which may require physically-based dynamically-coupled surface water and groundwater hydrological models to reliably describe these processes. Exemplarily, for a typical north-eastern Germany lowland catchment (Tollense river with about 400 km 2 ), an integrated hydrological model, MIKE SHE, coupled with a hydrodynamic model, MIKE 11, was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Waseem at el. [20] uses available low-frequency monitored flow and water quality data in combination with integrated hydrological and hydraulic modeling to represent the surface water and groundwater hydrology and NO 3 -N loads in the Tollense River catchment. The water balance results showed that 60-65% of total precipitation is lost via evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Waseem at el. [20] uses available low-frequency monitored flow and water quality data in combination with integrated hydrological and hydraulic modeling to represent the surface water and groundwater hydrology and NO 3 -N loads in the Tollense River catchment. The water balance results showed that 60-65% of total precipitation is lost via evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that groundwater modelling based on realistic assumptions on hydrogeological structure, boundary conditions, recharge and discharge areas can used as valuable tool for verification of the conceptual models accepted. There are four different process models, which integrate ground and surface water processes [4]. These models were compared based on own data requirement, desired complexity level, their ability to simulate relevant hydrologic and hydraulic processes.…”
Section: Introductionmentioning
confidence: 99%
“…This future climate scenario investigation approach is commonly based on the predictions of climate models and is deemed more scientific than directly assuming temperature and precipitation changes. The distributed hydrological model, MIKE SHE, has been widely used to simulate the runoff under different climates and underlying surface conditions (Waseem, Kachholz, Klehr, & Tränckner, 2020). It is the only integrated catchment modeling system in the MIKE series.…”
Section: Introductionmentioning
confidence: 99%